Exercise, immunology and upper respiratory tract infections - Peters, E. M. (International Journal of Sports Medicine, 1997)
The literature reveals a paradoxical response of the immune and host defense systems to endurance exercise apparent stimulation following long-term regular training and suppression in response to acute exposure to exhaustive endurance exercise. Several epidemiological surveys have confirmed a clinical manifestation of immunosuppression in the form of increased incidence of upper respiratory tract infection symptoms following participation in competitive marathon and ultramarathon running events. Prerace training status and racing intensity have been related to the incidence of this symptomatology during the postrace fortnight. Nutritional intervention studies have shown the antioxidant nutrient, vitamin C, to be effective in reducing the incidence of upper respiratory tract infection symptoms following competitive distance events. Laboratory studies have revealed this vitamin to be the first line of defense in neutralizing the auto-oxidative activity of phagocytes. It is hypothesized that exercise-induced neuroendocrine stimulation of the oxidative burst in neutrophils increases the rate of release of reactive oxygen species and that these are, in turn, neutralized by high plasma ascorbate levels. Enhancing intrinsic antioxidant defense by increasing exogenous antioxidant intake is thus theorized to be of long-term benefit to serious endurance athletes engaged in heavy training and competition.